Mediastinal Non-Hodgkin's Lymphoma Metastatic to Right Atrium Mimicking Right Atrial Myxoma - Khusnurrokhman, Gemilang; Wulandari, Laksmi (Folia Medica Indonesiana, 2021)
Highlight: • A 32-year-old male patient suffered mediastinal non-hodgkin's lymphoma metastatic to the right atrium which mimicked right atrial myxoma. • The patient died of suspected mediastinal NHL thromboembolism that spread in the right atrium. Abstract: In this case report, the anatomical pathology results in the form of B cell type LNH, but at the age of 32 years and the risk factor in this patient was a former active smoker. In the anatomical pathology results, the results of the B-High Grade Cell Type LNH were also obtained. B-cell type non-hodgkin's lymphoma can be mutated in the MYC gene (v-myc avian myceloctomatosis viral oncogene homolog) and the BCL-2 and BCL-6 (B-cell lymphoma) genes. If this morphology is found, then the patient's prognosis is poor. Most of these patients were males and the incidence was in the mediastinal area. Mediastinal NHL could develop and enlarge to involve the heart and pericardium. The spread could occur directly and lymphogens. These metastatic tumors were often misdiagnosed with atrial myxoma. In this case report, exploration of the right atrium and open mediastinal biopsy was performed. An open biopsy of the mediastinum revealed a mediastinal mass that enlarged to enter the right atrium. Atrial myxoma was not found. Primary lymphoma growth could also occur in the heart. This condition was called primary cardiac lymphoid (PCL). This case was very rare and was often considered an atrial myxoma. The patient died 10 days after discharge from the hospital. While the patient was eating, the patient had a seizure and the patient was immediately taken to the emergency department of Dr. Soetomo General Academic Hospital, Surabaya, and entered the ER (Resuscitation) ER room, but the patient died after being assisted for approximately two hours. Most likely the cause of the patient's death was a thromboembolic tumor in the right atrium that was released, so that it entered the bloodstream of the brain, causing the patient to have seizures. It was suspected that the cause of the patient's death was the presence of a tumor thrombus that separated into an embolism from the right atrium due to the large size of the tumor. Patients suffering from high rate NHL had a greater percentage of suffering from tumor thromboembolism as many as 10.6% compared to the Low type and Hodgkins lymphoma (LH) (5.8% and 7.25%).